Analisis Implementasi PSAK 101 dalam Penyusunan Laporan Keuangan pada Koperasi Syariah: Studi Fenomenologi pada BMT - Susanty, Widya; Majid, Shabri Abd; Sugianto (JSE: Jurnal Sharia Economica, 2025)
Accounting Standards Statement (PSAK) 101 in the preparation of financial reports in Islamic cooperatives, especially Baitul Maal wa Tamwil (BMT). The method used is the Systematic Literature Review (SLR) with the PRISMA 2020 approach. A total of 10 scientific articles published between 2015 and 2025 were analyzed to answer three main research focuses, namely: (1) the level of compliance of Islamic cooperatives with the provisions of PSAK 101, (2) components of financial reports that are not yet in accordance or have not been prepared, and (3) inhibiting and driving factors in the implementation of the standard. The results of the study show that the majority of Islamic cooperatives only prepare balance sheets and profit and loss statements, while other components such as temporary syirkah fund reports, ZIS reports, and trust funds are rarely disclosed. The main obstacles in the implementation of PSAK 101 include low literacy in Islamic accounting, the lack of integration of sharia-based financial information systems, and weak external supervision. However, there are initiatives and internal awareness from cooperative managers to improve the quality of financial reporting